2023
DOI: 10.1111/jpy.13329
|View full text |Cite
|
Sign up to set email alerts
|

Successional dynamics of the cultivated kelp microbiome

Abstract: Kelp are important primary producers that are colonized by diverse microbes that can have both positive and negative effects on their hosts. The kelp microbiome could support the burgeoning kelp cultivation sector by improving host growth, stress tolerance, and resistance to disease. Fundamental questions about the cultivated kelp microbiome still need to be addressed before microbiome‐based approaches can be developed. A critical knowledge gap is how cultivated kelp microbiomes change as hosts grow, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Nevertheless, the role of vertical transmission may be diminished due to increased exposure of external microbial communities to the environment (Härer & Rennison, 2023), alongside the associated wave-induced biofilm and blade erosion. Out-planted cultivated macroalgae also exhibit low levels of nursery-microbe persistence, with greater acquisition of environmental microbes, suggesting horizontal transmission is a major factor in shaping macroalgal microbiomes (K. M. Davis et al, 2023). In addition, recent work has shown that the microbial communities associated with macroalgal rafts are significantly disrupted relative to non-rafts, with a declining abundance of core microbes-suggesting that horizontal acquisition of microbes is a preferential strategy for microbial community assembly in Durvillaea (Pearman, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the role of vertical transmission may be diminished due to increased exposure of external microbial communities to the environment (Härer & Rennison, 2023), alongside the associated wave-induced biofilm and blade erosion. Out-planted cultivated macroalgae also exhibit low levels of nursery-microbe persistence, with greater acquisition of environmental microbes, suggesting horizontal transmission is a major factor in shaping macroalgal microbiomes (K. M. Davis et al, 2023). In addition, recent work has shown that the microbial communities associated with macroalgal rafts are significantly disrupted relative to non-rafts, with a declining abundance of core microbes-suggesting that horizontal acquisition of microbes is a preferential strategy for microbial community assembly in Durvillaea (Pearman, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Their prolific arsenal of bioactive compounds may benefit the host by shaping the microbiome and reducing biofouling of the surface (Lage and Bondoso, 2014; Graça et al ., 2016). Furthermore, other studies have shown that Pirellulaceae species are environmentally resilient and remain abundant in microbiomes from different kelp species and across habitats with variable abiotic conditions (Davis et al, 2023 Add Weigel and Pfister 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Examining shifts in the giant kelp microbiome composition as the host ages is crucial for understanding the host-microbiome relationship and the fate of exuded DOC. Previous studies on multiple macroalgal species have demonstrated significant local effects (Lin et al ., 2018; Weigel and Pfister, 2019; James et al ., 2020; Davis et al ., 2023), and our findings reveal clear depth and age effects. Depth-specific differences in the microbial communities associated with mature blades suggests potential a mechanism for differences DOC remineralization throughout the water column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20.599874 doi: bioRxiv preprint Seaweed-associated bacterial communities are far from static. Although a small core community can sometimes be identified, the bacteria form a highly dynamic community that fluctuates through time and space 13,14 . Abiotic factors, such as temperature, light, and salinity influence the community composition, as does the host itself [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%